PENERAPAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL DI BADAN LINGKUNGAN HIDUP PROPINSI SUMATERA UTARA - Farida Khairani Lubis (Universitas Islam Islam Sumatera Utara, 2018)
Government Regulation No. 71 of 2010 based on accruals will improve the quality of financialstatements and the realization of good governance besides knowing the performance of thegovernment. The enactment of Law Number 71 Year 2010 on Accrual-based Accounting Standards(SAP) brought significant changes in the financial reporting system. The changes are expected toprovide a complete picture of the financial position, present actual information about rights andobligations, and be useful in evaluating performance. This research is based on qualitativeinterpretative method. Data collection technique is encompassing observation, interview, anddocumentation. The results show that the Pemprovsu Environment Agency is implementingaccrual-based SAP in its 2016 financial statements and has carried out various trainings. Inaddition, there is a need to develop the understanding of financial managers of the EnvironmentalBoard of the provincial government about accrual-based SAP, such as socialization in the form ofseminars or discussions with other government agencies, as well as training related to the accrualbasedSAP.